Utilization of graphene as an alternative sustainable amendment in improving soil health through accelerated decomposition of oil palm mulch and enhanced nutrient availability - Khomphet, Thanet; Hussain, Tajamul (Frontiers in Agronomy, 2024)
Graphene has unique properties for improving soil health properties such as nutrient availability, soil physical and chemical properties, and controlled release of essential elements. This research aimed at determining the impact of graphene amendment on the decomposition of oil palm frond mulching and its impacts on soil health status. Study was conducted using a factorial experiment in completely randomized design with two main factors, i) covering condition: cover with plastic sheet and no cover, and ii) graphene application that included: T1 (Control): oil palm frond mulching (OFM), T2: OFM+ graphene (G), T3: OFM+G+ chemical fertilizer, and T4: OFM+G+ goat manure. The results Indicated that there were significant differences among graphene applications, between cover conditions, and for the interactions between graphene applications and cover conditions for all soil characteristics in the most observed month. In the third month of soil analysis, the treatment of graphene applications showed higher electrical conductivity (T2: 151.7±6.8 µS cm -1 ), available phosphorus (T3: 9.0±6.7 mg kg -1 ), exchangeable potassium (T2: 67.1±24.9 mg kg -1 ), and exchangeable calcium (T3: 95.4±5.1 mg kg -1 ), compared to control. Cover condition showed suitable soil pH (5.0±0.2), higher soil available phosphorus (7.1±5.0 mg kg -1 ), and exchangeable calcium (599.1±235.2 mg kg -1 ), but no cover condition presented higher soil organic matter (0.7±0.2%), exchangeable potassium (60.3±19.1 mg kg - 1 ), and exchangeable magnesium (96.7±11.4 mg kg -1 ). Correlation results indicated that most soil characteristics were correlated under graphene applications. The principal component analysis showed that the treatments of graphene application dominated in most soil characteristics. The results suggest that graphene has potential for improving soil health properties and can be applied as an alternative sustainable amendment to accelerate the decomposition of oil palm frond mulch and enhanced nutrient availability for oil palm. In addition, authors suggest further investigations should consider more soil health parameters in long-term field studies for better understandings and recommendations to farmers.